2022
DOI: 10.1155/2022/5526827
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid MPC-Based Automatic Generation Control for Dominant Wind Energy Penetrated Multisource Power System

Abstract: This paper presents hybrid model predictive control-based automatic generation regulator design for dominant wind energy penetrated multisource power system. The other power generation sources hydro and thermal are also considered in each area. The proposed AGC regulator is designed for each independent area considering only local power system states to ensure the stability of closed-loop system under small perturbation. The performance of the proposed AGC regulator has been validated for 2% step load perturba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…These data are then used to learn the type-2 fuzzy system (based on a neural network or using evolutionary algorithms). For more information on the type-2 fuzzy system and its equations, see [35,36].…”
Section: Predictive Controller Designmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are then used to learn the type-2 fuzzy system (based on a neural network or using evolutionary algorithms). For more information on the type-2 fuzzy system and its equations, see [35,36].…”
Section: Predictive Controller Designmentioning
confidence: 99%
“…Some researchers have also used secondary frequency control over the converter of renewable energy production sources to control the frequency [34]. One of the control methods that has been successful in all engineering fields is model predictive control (MPC) [35,36]. This control method is based on predicting the system behavior (from the mathematical model of the system) and generating a control signal to minimize the error.…”
Section: Introductionmentioning
confidence: 99%
“…In [11],a cascade-fractional order secondary controller is suggested to reach the goals of the AGC when the system integrated with renewables. A hybrid MPC is suggested in [12] to reach the goals of the AGC when the system integrated with renewables.…”
Section: Introductionmentioning
confidence: 99%
“…With a typical controller set to a single functional form, it isn't easy to establish stability across the system's whole working range due to its nonlinearity. To solve this problem and efficiently run the power generating units, frequency, and tie-line power flow, intelligent control technology such as the FLC is advised over the traditional one [15]. The Fuzzy logic controller increases the traditional controller's closed-loop effectiveness and can manage every variation in operational points by modifying controller parameters live.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers' primary focus in the combined AGC experiments has been designing the ALFC loop controller. The auxiliary controller of the ALFC loop, like traditional PID, fuzzy-PID, and Neuro-fuzzy-PID, with HVDC, has been done in the integrated LFC and automatic voltage regulator (AVR) inner loops in the work done in [15,16]. Abazari et al [17] demonstrated load frequency control Power Systems using a classical PID & Fuzzy PID controller.…”
Section: Introductionmentioning
confidence: 99%